Supervisi Bimbingan Konseling dalam Meningkatkan Penguasaan Keterampilan Layanan Konseling Guru BK - Amelisa, Maya; Suhono, Suhono (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2018)
In improving the mastery of Teacher of Counselling and Guidance’s service skill requires counselling and guidance supervision. In implementing this supervision, the most common agreement is to make contact section with a supervised client for several time periods. There is a model of the supervision process which is very useful to explain some of these issues that is by analyzing the reflection of the counselling process. Focus of this level is the client by analyzing what is said, how the various parts of client’s life is interlocked, and what the client wants from the oversight of the supervisor’s feelings in response. The grabbed information provided a guidance to see the cases which unconsciously can be articulated by supervisors. This library research was performed to explain the best method which can be applied by supervisors in conducting supervision to their client.